A review of the Carboniferous and Permian trilobites of Australia - Vanderlaan, Tegan A.; Ebach, Malte C. (Zootaxa, 2015)
The first complete review of the Carboniferous and Permian trilobite species found within Australia is presented to assess the current standing of Australian taxa in a modern systematic context. The review consists of four families, 20 genera and 61 known species from the early Tournaisian to Moscovian (358.9 Ma to 304 Ma), throughout New South Wales, Tasmania, Western Australia and Queensland. The revision also includes a revised anatomical nomenclature for Australian Carboniferous trilobites. Emended diagnoses are provided for seven genera and 28 species. The genus Thalabaria is placed within the subfamily Archegoninae, and the genera Australokaskia and Planokaskia are placed within Cummingellinae. The subgenera Brachymetopus (Spinimetopus), Bollandia (Capricornia), Australokaskia (Longilobus) and Australokaskia (Planilobus) are suppressed within Brachymetopus, Bollandia, Australokaskia, respectively. All Brachymetopus (Brachymetopus) maccoyi subspecies are elevated to species. Species of Linguaphillipsia are considered sensu lato until there is adequate revision of the entire genus. New combinations include the following: Aprathia semicircularis is reassigned to Weania; Aprathia applanata is questionably reassigned to Carbonocoryphe; and Phillipsia squamata is tentatively reassigned to Palaeophillipsia. The following have been synonymised: Conophillipsia with Monodechenella; Megaproetus with Pudoproetus; Weberiphillipsia with Palaeophillipsia; Weania (Rosehillia) with Schizophillipsia; Conophillipsia breviceps dungogensis with Monodechenella breviceps; Linguaphillipsia raglanensis with Linguaphillipsia stanvellensis; and Weberiphillipsia girvanensis with Palaeophillipsia collinsi. Carbonocoryphe (Winterbergia) elegans, Carbonocoryphe (Winterbergia) keepitensis and Winterbergia? waterhousei are considered representatives of indeterminate genera.